Factors influencing rain acidification from volcanic sulphur in Iceland - Stefani, Martina, 1983- (2018)
In the past decades, acid rain has been recognized as a detrimental to numerous ecosystems. Rainwater acidity can be impacted by various sources e.g. anthropogenic emissions, biogenic release, sea spray, soil dust and volcanic emissions. One of the main contributors to acid rain is sulphuric acid which can be of anthropogenic or natural origins. The main aim of this study is to estimate possible dispersion and environmental pressure caused by sulphur dioxide (SO2) release during the Holuhraun eruption in Iceland from 31 August 2014 to 27 February 2015 by analyzing a dataset of chemical analysis of precipitation samples collected during the eruption period. The main acidifying component was identified being SO42-, but a simple relationship between high SO42-concentrations and low pH values could not be found. Geographical, geochemical and meteorological factors are analyzed to identify their influence and the involved processes. Geographical factors such as distance from the eruption source, altitude and latitude do not seem to influence the distribution of sulphate in the precipitation samples. The distance from the sea shore influences the occurrence of sea-salt derived sulphur in addition to the volcanogenic sulphur. The precipitation amount influences the dilution of chemical species with lower rainfall resulting in higher ionic concentration of the chemical species. The dispersion model HYSPLIT from NOAA was used to calculate the wet deposition over the first four months of the eruption, from September to December 2014. The aim was to see if a simple and easy to use numerical model could be used as a tool to forecast wet deposition of sulphate. The results of the numerical modelling were then compared to the collected rain samples showing a 50% accordance between model and measurements. The analysis shows that refining the model is however necessary, by adding a chemical module and additional data about chemical transformation rates in order to obtain a powerful, free and easy to use tool in case of future ...